Bender Gestalt Visual-Motor test – Sistema de Pontuação Gradual (B-SPG): A study with different samples - Noronha, Ana Paula Porto; Rueda, Fabian Javier Marin; Santos, Acacia Aparecida Angeli dos (Paidéia (Ribeirão Preto), 2013)
The aim in this study was to analyze differences between children’s performances on the Bender – Sistema de Pontuação Gradual (B-SPG) [Gradual Scoring System] in the states of Minas Gerais and Paraíba, and to compare them with the results presented in the test manual. The participants were 511 children, both sexes, aged 6-10 years ( M = 8.21, SD = 1.33), and 50.7% male. The children were from two states, Minas Gerais ( n = 298, 58.3%) and Paraiba ( n = 213, 41.7%). The SPG was administered collectively in classrooms. The mean B-SPG scores between the children from Minas Gerais and Paraiba were very similar and not statistically significant. Regarding the comparison between the two states and the normative sample, three results were significant, two of which favored the children from São Paulo and the other the children from Minas Gerais and Paraíba, showing little variation in the results of the B-SPG.